A method for improving the ion conductivity of a wet-process ultra-high molecular weight polyethylene separator

CN123018343APending Publication Date: 2026-10-30JIANGSU HORIZON NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611301451.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

同步拉伸产线中尚缺乏将热处理嵌入同步拉伸工序的技术方案

Benefits of technology

1、离子电导率显著提升:通过同步双拉过程中的动态热处理诱导形成双向均匀取向的微孔结构,结合萃取后二次横向拉伸对孔型的进一步优化,为锂离子提供了更规整、连续的传输通道,能够显著提高隔膜的离子传输性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1787711545147-000001
    Figure REF-OBJ-1787711545147-000001
Patent Text Reader

Abstract

The application belongs to the technical field of lithium ion battery separator preparation, and particularly relates to a preparation method for improving ion conductivity of a wet-process ultra-high molecular weight polyethylene (UHMWPE) separator by synergistic regulation of a heat treatment process and a synchronous stretching process. The heat treatment process and the synchronous biaxial stretching process are integrated designed, a "tension-relaxation" cycle (dynamic heat treatment) is introduced in the high-temperature section of the synchronous stretching, the characteristics of MD and TD simultaneous orientation during synchronous biaxial stretching are utilized, in-situ regulation of crystal structure in a biaxial stress field and fine tailoring of microporous structure are realized, and finally the ion conductivity of the separator is significantly improved on the premise of maintaining good mechanical properties of the separator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery separator preparation technology, specifically relating to a method for improving the ionic conductivity of wet-process ultra-high molecular weight polyethylene (UHMWPE) separators through the synergistic control of heat treatment and synchronous stretching processes. Background Technology

[0002] Wet process (thermally induced phase separation, TIPS) is currently the mainstream technology for preparing high-end lithium-ion battery separators. Based on the stretching method, wet process is divided into two technical routes: asynchronous biaxial stretching and synchronous biaxial stretching. Among them, synchronous stretching technology can simultaneously orient in both the transverse and longitudinal directions, resulting in better thickness uniformity and balanced mechanical properties, and has become the mainstream production process for high-end wet process separators.

[0003] Existing heat treatment processes have the following shortcomings: The heat treatment and stretching processes are disconnected: In existing technologies, heat treatment is usually completed as a separate preparatory process before stretching, and the two lack deep coupling. The regulatory effect of heat treatment on crystal structure fails to form a synergistic effect with the stress field during stretching.

[0004] The targeted optimization of ionic conductivity has not been addressed: Existing studies mainly focus on the improvement of pore size and mechanical properties by heat treatment, and have not yet established a direct link between the synergistic regulation of heat treatment and stretching and the improvement of membrane ionic conductivity.

[0005] The "Dynamic Heat Treatment-Synchronous Stretching Integration" pathway is lacking: Although some patents propose the idea of ​​high-temperature heat treatment after extraction, the heat treatment and stretching processes are still sequential, failing to achieve process integration. There is currently a lack of technical solutions in synchronous stretching production lines that embed heat treatment into the synchronous stretching process. Summary of the Invention

[0006] To overcome the shortcomings of existing technologies, this invention aims to provide a method for preparing wet-process UHMWPE membranes with improved ionic conductivity. By integrating the heat treatment process with the simultaneous biaxial stretching process, a "tension-relaxation" cycle (dynamic heat treatment) is introduced in the high-temperature section of the simultaneous stretching. Utilizing the characteristic of simultaneous MD and TD orientation during biaxial stretching, in-situ control of the crystal structure and fine tailoring of the microporous structure are achieved in the biaxial stress field. Ultimately, while maintaining the membrane's good mechanical properties, its ionic conductivity is significantly improved.

[0007] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: A method for preparing a wet-process ultra-high molecular weight polyethylene (UHMWPE) membrane with improved ionic conductivity includes the following steps: (1) Low-temperature casting molding of UHMWPE: UHMWPE with a viscosity-average molecular weight of 1.5 million to 3 million is mixed with white oil at a mass ratio of 20 to 30: 70 to 80. The mixture is melt-blended at 200 to 230°C using a twin-screw extruder. After extrusion through a T-die, the mixture is rapidly cooled and formed on a casting roller to obtain UHMWPE / white oil sheet with a thickness of 1.5 to 2.5 mm. (2) The sheet from the previous step is stretched longitudinally to obtain a diaphragm; (3) The previous membrane is subjected to synchronous biaxial stretching with dynamic heat treatment to obtain a synchronously stretched membrane; including a preheating section, a dynamic heat treatment section and a final stretching section; the dynamic heat treatment section includes: at a temperature of 115~125℃, a “stretch-hold-relax-hold” cycle operation is performed simultaneously along MD and TD, the number of cycles is 2~5 times; holding time: 30~120 seconds; relaxation range: synchronously retracted in the MD and TD directions to 0.85~0.95 times the size after stretching; (4) The synchronous stretching film is stretched laterally in one step to obtain the stretching film; (5) Extraction and drying to obtain a diaphragm; (6) Perform a second transverse stretching of the diaphragm; (7) Heat setting and winding to obtain the final product.

[0008] Preferably, the technical approach adopted in this invention is as follows: Low-temperature casting controls initial crystal morphology → longitudinal stretching imparts initial orientation → simultaneous double stretching with dynamic heat treatment → first transverse stretching → extraction to remove white oil → second transverse stretching → heat setting to fix the hole structure Preferably, after extrusion through a T-die, the material is rapidly cooled and formed on a casting roll, with the temperature of the cooling roll controlled at 5~15℃ and the winding speed at 5~6 m / min, to obtain a UHMWPE / white oil sheet with a thickness of 1.5~2.5 mm. Preferably, the temperature of the cooling roll is controlled at 8~10℃. Preferably, the viscosity-average molecular weight of UHMWPE is 2 million to 2.5 million; the mass ratio of UHMWPE to white oil is 25 to 28: 72 to 75.

[0009] Preferably, the winding speed is 5.5~6 m / min; Preferably, a UHMWPE / white oil sheet with a thickness of 2~2.5 mm is obtained.

[0010] Preferably, the blending melting temperature is 215~220℃.

[0011] Preferably, the longitudinal stretching operation in step two is as follows: The sheet obtained in step one is introduced into a longitudinal stretching device and stretched along the longitudinal direction (MD) at a temperature of 100~120℃, with a stretching ratio of 2~4 times.

[0012] Preferably, the sheet is introduced into a longitudinal stretching device and stretched to 3 to 3.5 times its original size along the MD direction at a temperature of 110 to 115°C; Preferably, the simultaneous biaxial stretching operation process including dynamic heat treatment in step three is as follows: The longitudinally stretched film obtained in step two is introduced into a synchronous biaxial stretching device for simultaneous orientation in both the transverse and longitudinal directions, and a tension-relaxation cycle is introduced during this process: (1) Preheating section: Heat the diaphragm to 125~135℃ to soften it evenly; (2) Dynamic heat treatment section: where: Single stretching amplitude: Simultaneously stretch to 1.2 to 1.4 times the initial size in both the MD and TD directions, preferably 1.2 to 1.3 times, and more preferably 1.25 to 1.3 times; the size of the membrane in both the MD and TD directions at the beginning of each cycle is taken as the initial size of that cycle.

[0013] Holding time: 30~120 seconds; specifically, the first holding time after stretching is 30~120 seconds; preferably 45~60 seconds; The second holding time after relaxation is 30 to 120 seconds, preferably 30 to 60 seconds.

[0014] Preferably, the relaxation range is: the MD and TD directions simultaneously retract to 0.88~0.9 times the stretched size; (3) Final stretching stage: The final synchronous biaxial stretching is completed at 105~125℃, with a total stretching ratio of 2×2~3×3 (MD×TD). After the dynamic heat treatment stage, the cumulative size ratio of the membrane in the MD and TD directions relative to the initial size ratio in step (3) is less than the final synchronous stretching ratio in the corresponding directions.

[0015] In a preferred embodiment of the present invention, the "stretch-hold-relax-hold" cycle is repeated 3 to 4 times.

[0016] Preferably, the fourth step of the transverse stretching operation is as follows: The synchronously stretched film obtained in step three is subjected to transverse (TD) stretching at a temperature of 115~125℃, with a stretching ratio of 6.5~7.0 times.

[0017] Preferably, the synchronously stretched film obtained in step three is subjected to transverse (TD) stretching at a temperature of 118~120℃, with a stretching ratio of 6.8~7.0 times.

[0018] Preferably, the extraction and drying process in step five is as follows: The stretched membrane obtained in step four is passed through an extraction device using dichloromethane as the extractant. The temperature inside the extraction device is controlled at 20-40°C, and the diaphragm is kept under appropriate tension during the extraction process. The extracted diaphragm is then dried with hot air at 40-60°C to remove any residual extractant.

[0019] Preferably, the stretched membrane obtained in step four is passed through an extraction device using dichloromethane as the extractant. The temperature inside the extraction device is controlled at 25-40°C, and the diaphragm maintains appropriate tension during the extraction process. The extracted diaphragm is then dried with hot air at 40-50°C to remove residual extractant.

[0020] Preferably, the operation process of the second transverse stretching in step six is ​​as follows: The extracted and dried diaphragm was subjected to a second transverse stretching at a temperature of 100~130℃, with a stretching ratio of 1.5~2.0 times.

[0021] Preferably, the extracted and dried diaphragm is subjected to a second transverse stretching at a temperature of 115~120℃, with a stretching ratio of 1.8~2.0 times.

[0022] Step 7: Heat setting The diaphragm after secondary transverse stretching is heat-set at 115~130℃. During the heat-setting process, the membrane surface tension is maintained to release residual internal stress and fix the final pore structure.

[0023] Preferably, the diaphragm after secondary transverse stretching is heat-set at 125~130℃, maintaining membrane surface tension during the setting process to release residual internal stress and fix the final pore structure. Preferably, the heating temperature of the preheating section in step three is 128~130℃.

[0024] Preferably, the final total TD stretch ratio is controlled within 45, and the total MD stretch ratio is controlled within 15. Compared with the prior art, the beneficial effects of the present invention are as follows: 1. Significantly improved ionic conductivity: The dynamic heat treatment during the synchronous double stretching process induces the formation of a bidirectional uniformly oriented microporous structure. Combined with the secondary lateral stretching after extraction to further optimize the pore shape, it provides a more regular and continuous transport channel for lithium ions, which can significantly improve the ion transport performance of the membrane.

[0025] 2. Narrower and more uniform pore size distribution: MD and TD are oriented simultaneously during the synchronous bi-stretching process, avoiding the structural inhomogeneity that may be caused by asynchronous stretching and step-by-step orientation; the tension-relaxation cycle in dynamic heat treatment further promotes the uniform fusion of the polymer-depleted phase, which significantly reduces the pore size distribution coefficient (Span value) of the final membrane.

[0026] 3. Avoid excessive coarsening of pore structure: Compared with traditional long-term static heat treatment, dynamic heat treatment can achieve structural control while avoiding safety risks caused by excessive increase in pore size.

[0027] 4. Highly compatible with synchronous stretching production lines: The dynamic heat treatment process is integrated into the synchronous double stretching process without the need to add independent equipment or change the production line layout. It is friendly to the transformation of existing synchronous stretching production lines and is easy to promote industrially. Detailed Implementation

[0028] The present invention is illustrated below with reference to examples, but is not intended to limit the invention. Any simple substitutions or modifications made to the present invention by those skilled in the art are within the scope of the technical solutions protected by this invention.

[0029] Example 1: Step 1: Mix UHMWPE powder with a viscosity-average molecular weight of 2 million with white oil at a mass ratio of 25:75, melt-blend at 220°C using a twin-screw extruder, and then cast on a cold roller at 10°C with a winding speed of 5.5 m / min to obtain a UHMWPE / white oil sheet with a thickness of 2.0 mm.

[0030] Step 2: Introduce the sheet into the longitudinal stretching equipment and stretch it to 3 times its original size along the MD direction at a temperature of 110℃.

[0031] Step 3: Introduce the longitudinally stretched film into the synchronous biaxial stretching equipment, and preheat it to 130°C in the preheating section; then perform three "tension-relaxation" cycles at 120°C, with simultaneous operation in the MD and TD directions: Stretch to 1.3 times the initial size and hold for 60 seconds; Simultaneously retract to 0.90 times the stretched size and hold for 30 seconds.

[0032] After completing the cycle, the material is finally stretched synchronously at 115°C to a total magnification of 3×3 (MD×TD).

[0033] Step 4: Perform a transverse stretching of the synchronous stretching film at 120°C, with a stretching ratio of 6.8 times.

[0034] Step 5: Extract the stretched diaphragm with dichloromethane at a temperature of 25°C, maintaining appropriate tension on the diaphragm during extraction. Dry the extracted diaphragm with hot air at 50°C.

[0035] Step 6: The extracted and dried diaphragm is subjected to a second transverse stretching at 120°C, with a stretching ratio of 1.8 times.

[0036] Step 7: Heat set at 125℃.

[0037] Performance testing 1. Porosity was determined using the electronic balance method, referring to standard GB / T 36363-2018.

[0038] 2. The average pore size and pore size distribution coefficient were determined using the compressed air method.

[0039] 3. Ionic conductivity reference standard GB / T 36363-2018.

[0040] 4. Diaphragm thickness: GB / T 6672-2001 ISO4593:1993. Thickness testing was performed using a Malcolm thickness gauge.

[0041] 5. Tensile strength and elongation shall be determined according to the method of GB / T 36363-2018.

[0042] Performance test results: Membrane thickness: 6.1 μm Porosity: 41.6% Average pore size: 38 nm Aperture distribution coefficient (Span): 0.82 Room temperature ionic conductivity: 1.72 mS·cm -1 .

[0043] Example 2: Step 1: Mix UHMWPE powder with a viscosity-average molecular weight of 2.5 million with white oil at a mass ratio of 28:72. Melt-blend the mixture at 215°C using a twin-screw extruder. After extrusion, cast the mixture on a cold roller at 8°C with a winding speed of 6.0 m / min to obtain a UHMWPE / white oil sheet with a thickness of 2.0 mm.

[0044] Step 2: Introduce the sheet into the longitudinal stretching equipment and stretch it to 3.5 times its original length along the MD direction at a temperature of 115℃.

[0045] Step 3: Introduce the longitudinally stretched film into the synchronous biaxial stretching equipment, and preheat it to 128°C; then perform 4 "tension-relaxation" cycles at 118°C, with synchronous operation in both the MD and TD directions: Stretch to 1.25 times the initial size and hold for 45 seconds; Simultaneously retract to 0.88 times the stretched size and hold for 30 seconds.

[0046] After completing the cycle, the material is finally stretched synchronously at 110°C to a total magnification of 2×2 (MD×TD).

[0047] Step 4: Perform a transverse stretching of the synchronous stretching film at 118°C, with a stretching ratio of 7.0 times.

[0048] Step 5: Extract the stretched diaphragm with dichloromethane at a temperature of 25°C, maintaining appropriate tension on the diaphragm during extraction. Dry the extracted diaphragm with hot air at 50°C.

[0049] Step 6: The extracted and dried diaphragm is subjected to a second transverse stretching at 115°C, with a stretching ratio of 2.0 times.

[0050] Step 7: Heat set at 125℃.

[0051] Performance test results: Membrane thickness: 5.9 μm Porosity: 42.8% Average pore size: 35 nm Aperture distribution coefficient (Span): 0.76 Room temperature ionic conductivity: 1.77 mS·cm -1 .

[0052] Comparative Example 1 (Conventional synchronous stretching process, without dynamic heat treatment) Step 1: Same as Step 1 in Example 1.

[0053] Step 2: Same as Step 2 in Example 1.

[0054] Step 3: The longitudinally stretched film is introduced into the synchronous biaxial stretching equipment and heated to 130°C in the preheating section; the longitudinally stretched film is directly synchronously biaxially stretched to 3×3 at 115°C without dynamic heat treatment cycle.

[0055] Steps four through seven: Same as steps four through seven in Example 1.

[0056] Performance test results: Membrane thickness: 6.3 μm Porosity: 43.6% Average pore size: 41 nm Aperture distribution coefficient (Span): 1.30 Room temperature ionic conductivity: 1.36 mS·cm -1 .

[0057] Comparative Example 2 (no preheating section, direct dynamic heat treatment) Step 1: Same as Step 1 in Example 1.

[0058] Step 2: Same as Step 2 in Example 1.

[0059] Step 3: The longitudinally stretched film is introduced into the synchronous biaxial stretching equipment. Without preheating, it directly enters the 120℃ dynamic heat treatment zone for three "tension-relaxation" cycles. The MD and TD directions are operated synchronously, and the cycle parameters are the same as in Example 1. After the cycle is completed, it is finally synchronously stretched to a total ratio of 3×3 (MD×TD) at 115℃.

[0060] Steps four through seven: Same as steps four through seven in Example 1.

[0061] Performance test results: Membrane thickness: 6.0 μm Porosity: 40.8% Average pore size: 44 nm Aperture distribution coefficient (Span): 1.18 Room temperature ionic conductivity: 1.48 mS·cm -1 .

[0062] Comparative Example 3 (Dynamic heat treatment, no shrinkage, maintaining operation) Step 1: Same as Step 1 in Example 1.

[0063] Step 2: Same as Step 2 in Example 1.

[0064] Step 3: Introduce the longitudinally stretched film into the synchronous biaxial stretching equipment and heat it to 130°C in the preheating section; complete 3 stretching operations at 120°C, with synchronous operation in the MD and TD directions, stretching to 1.3 times the initial size each time, without synchronous retraction and holding operation, and then directly synchronously biaxially stretch to 3×3 at 115°C.

[0065] Steps four through seven: Same as steps four through seven in Example 1.

[0066] Performance test results: Membrane thickness: 6.1 μm Porosity: 41.9% Average pore size: 42 nm Aperture distribution coefficient (Span): 1.15 Room temperature ionic conductivity: 1.51 mS·cm -1 .

[0067] Performance Comparison Summary Table

[0068] The results show that: 1. The ionic conductivity of Examples 1 and 2 is significantly better than that of the comparative example.

[0069] 2 Compared with the conventional synchronous stretching process without dynamic heat treatment (Comparative Example 1), the ionic conductivity is increased by about 26%~30%, and the Span value is reduced by about 37%~42%. Although Comparative Example 1 has a larger thickness (6.3 μm) and higher porosity (43.6%), the lack of dynamic heat treatment results in disordered pore structure, wide pore size distribution, and low ion transport efficiency.

[0070] 3. Compared to the process of directly performing dynamic heat treatment without a preheating section (Comparative Example 2), the ionic conductivity increased by approximately 16%–20%, and the Span value decreased from 1.18 to 0.76–0.82. In Comparative Example 2, due to the lack of a preheating section, the membrane entered the dynamic heat treatment directly in an insufficiently softened state, resulting in uneven response of the molecular chains during the "tension-relaxation" cycle, increased pore size (44 nm) and wider distribution (Span = 1.18), thus limiting the improvement in ionic conductivity. This indicates a significant synergistic effect between sufficient softening in the preheating section and dynamic heat treatment.

[0071] 4. (Comparative Example 3) In the dynamic heat treatment without relaxation and holding operations, the pore size increased (42 nm) and the distribution was wider (Span=1.15), but the improvement in ionic conductivity was limited. This indicates that there is a significant synergistic effect among stretching-holding-relaxation-holding in dynamic heat treatment.

[0072] 5. Under the conditions of a thickness of 5.9~6.1μm and a porosity of approximately 42%, the embodiments of the present invention achieved a flux density of 1.72~1.77 mS·cm. -1 The ionic conductivity reflects the significant improvement in ion transport performance resulting from the synergistic effect of dynamic heat treatment and multi-stage stretching. Among them, Example 2 (5.9 μm), with its thinner thickness, achieved the highest ionic conductivity (1.77 mS·cm) due to its shorter ion transport path and the uniform pore structure formed by dynamic heat treatment. -1 Furthermore, under similar thickness conditions, it exhibits comparable tensile strength to existing products.

[0073] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several modifications and improvements without departing from the inventive concept of the present invention, and these all fall within the protection scope of the present invention.

Claims

1. A method for preparing a wet-process ultra-high molecular weight polyethylene (UHMWPE) membrane with improved ionic conductivity, characterized in that, Includes the following steps: (1) Low-temperature casting molding of UHMWPE: UHMWPE with a viscosity-average molecular weight of 1.5 million to 3 million is mixed with white oil at a mass ratio of 20 to 30: 70 to 80. The mixture is melt-blended at 200 to 230°C using a twin-screw extruder. After extrusion through a T-die, the mixture is rapidly cooled and formed on a casting roller to obtain UHMWPE / white oil sheet with a thickness of 1.5 to 2.5 mm. (2) The sheet from the previous step is stretched longitudinally to obtain a diaphragm; (3) The previous membrane was subjected to synchronous biaxial stretching with dynamic heat treatment to obtain a synchronously stretched membrane; It includes a preheating section, a dynamic heat treatment section, and a final stretching section; the dynamic heat treatment section includes: performing a "stretch-hold-relax-hold" cycle operation simultaneously along MD and TD at a temperature of 115~125℃, with 2~5 cycles; holding time: 30~120 seconds; relaxation range: synchronously retracting in the MD and TD directions to 0.85~0.95 times the stretched size; the single stretching range of the dynamic heat treatment section in step (3) is: synchronously stretching in the MD and TD directions to 1.2~1.4 times the initial size; (4) The synchronous stretching film is stretched laterally in one step to obtain the stretching film; (5) Extraction and drying to obtain a diaphragm; (6) Perform a second transverse stretching of the diaphragm; (7) Heat setting and winding to obtain the final product.

2. The preparation method according to claim 1, characterized in that, In step (1), the temperature of the cold roller is controlled at 5~15℃ and the winding speed is 5~6 m / min.

3. The preparation method according to claim 1, characterized in that, Step (2) specifically includes: introducing the sheet obtained in step (1) into a longitudinal stretching device, stretching it longitudinally at a temperature of 100~120℃, with a stretching ratio of 2~4 times, to obtain a film.

4. The preparation method according to claim 1, characterized in that, The preheating section of step (3) specifically includes: heating the diaphragm to 125~135℃ to make it soften uniformly.

5. The preparation method according to claim 1, characterized in that, The final stretching section in step (3) is specifically completed at 105~125℃.

6. The preparation method according to claim 1, characterized in that, The total stretching ratio of MD×TD in step (3) is 2×2~3×3.

7. The preparation method according to claim 1, characterized in that, The step (4) specifically includes: performing transverse stretching at a temperature of 115~125℃, with a stretching ratio of 6.5~7.0 times.

8. The preparation method according to claim 1, characterized in that, The extractant in step (5) is dichloromethane, the extraction temperature is 20~40℃, and the drying is hot air drying at 40~60℃.

9. The preparation method according to claim 1, characterized in that, The step (6) specifically includes: stretching the extracted and dried diaphragm twice in the transverse direction at a temperature of 100~130℃, with a stretching ratio of 1.5~2.0 times.

10. The preparation method according to claim 1, characterized in that, The heat setting temperature is 115~130℃.